2002
DOI: 10.1007/s007010200066
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical DREZotomy for Pain of Spinal Cord and Cauda Equina Injury Origin: Clinical Characteristics of Pain and Implications for Surgery in a Series of 26 Patients

Abstract: The result of the DREZotomy procedure used for the treatment of chronic intractable neuropathic pain caused by injuries at the T9-L4 spine level in 26 patients has been reported. For the purpose of identifying the most favorable pain pattern for DREZ surgery we retrospectively analyzed the effectiveness of surgical treatment on different forms of pain in the follow-up period of 13-50 months, 37 months on average. All pain forms were classified according to subjective sensory pain expression including the rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
7

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 8 publications
0
32
0
7
Order By: Relevance
“…One study conducted a prospective controlled trial, 14 1 utilized a pre-post study design, 9 and 9 studies utilized a case series study design [6][7][8][15][16][17][18][19][20] (see Table 2). In each study, an intervention for pain was administered to an individual with SCI, and the change in pain was measured; only 1 study compared treated individuals with those in a control group.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study conducted a prospective controlled trial, 14 1 utilized a pre-post study design, 9 and 9 studies utilized a case series study design [6][7][8][15][16][17][18][19][20] (see Table 2). In each study, an intervention for pain was administered to an individual with SCI, and the change in pain was measured; only 1 study compared treated individuals with those in a control group.…”
Section: Methodsmentioning
confidence: 99%
“…6,9,19,20 Sindou's technique for MDT involves selectively destroying nociceptive fibers and hyperactive neurons, which interfere with the neurogenic mechanism causing pain. 20 Chun et al 9 reported on 38 individuals treated with the procedure between 2003 and 2008.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations